High-grade cervical intraepithelial lesions among HIV infected patients - Silva, Ricardo J.O.; Reis, Aldo F.F.; Russomano, Fábio B.; Fialho, Susana C.A.V.; Grinsztejn, Beatriz; Athay, Maria José P.M. (Brazilian Journal of Sexually Transmitted Diseases, 2003)
Introdution: It has not been demonstrated yet how HIV infection increases canceris incidence. Although squamous cell carcinoma is strongly associated to infection, only cervical câncer can bc classified as aids definer. Objective: To study the prevalence of high grade cervical intraepithelial lesions and the influence of clinical, laboratorial and behavioral variables in HIV infected patients. Methods: From a total of 420 patients infected by HIV assisted in public healthcare instituitions from 1996 to 2000, 354 attendcd the data system for analysis. The colposcopy was sistematically made in all patients. The presence of high-grade cervical intraepithelial lesions (HSIL) was compared with available variables. The high-grade lesions diagnosis was obtained in material analysed in histopatology while some colpocitologic aspects of B, C patterns and some E pattern (Roma colposcopic classification, 1990) wcrc bcing observcd. Resuits: The prevalence of high-grade lesions was 7.9%. The variables that were significant in the multivariate analysis were: CD4 lower lhan 350 cel/mm3 OR = 2.62 [Cl 95%: 1.13-6.10], tabagism OR - 2.72 [Cl 95%: 1.2-6.21] and age lower than 33 years old OR = 2.56 [Cl 95%: 1.1-5.96]. Conclusion: It is high the prevalence of high-grade cervical intraepithelial lesions in patients infected by HIV. Imunodeficience, tabagism and age lower than 33 years old were the variables associated to the presence of these lesions.